The Evolutionism in the work of Uroš Milanković - Ilinčić, Aleksandar (Sociološki pregled, 2024)
With the assumption that the work of the intellectual Uroš Milanković (1800–1849) can be marked as pioneering in terms of the beginning of the evolutionist idea within Serbian philosophical and sociological heritage, the paper analyses the overall influences of evolutionism as a theory. Besides explaining general characteristic of evolutionism and comparing Milanković’s historical appearance in that context, the article also points to the interdependence of the formation of evolutionist tendencies and their reflections on society. In this manner, the research not only reexamines Milanković’s individual work and confirms the perception of him as a herald of evolutionism in Serbian culture, but it also uses the interdisciplinary approach which includes the analysis of Milanković’s writings and comparison with other theoreticians, giving a more complex assessment of the development of evolutionism in this era.
Keywords: Uroš Milanković; evolutionism; evolution; sociology; philosophy